Perlindungan Hukum Bagi Korban Penyitaan Akun Media Sosial dalam Perspektif Hukum Positif - Alicia Radefi; Akbar Dwi Saputra; Yeni Widowaty (Media of Law and Sharia, 2024)
Criminal acts with electronic media in the cyber world are known as cybercrime. Humiliation, reputation pollution, social media fraud are some examples of cybercrime. The most widely used means of cybercrime can be used as evidence to strengthen evidence in court proof. In this case, the author will discuss the settlement of the account suspension, the procedure of the Account suspension and how the legal protection against the victims of the accounts suspension. This writing uses a method of normative jurisprudence, which covers research on the level of synchronization of law, research on legal systematics, and research into the foundations of law. The seizure of social media accounts as evidence in the proof process is permitted because the social media account is an object or something that is directly used in committing a criminal act on social media (cybercrime) and has a clear legal basis of regulation that is the ITE Act. Arrangements regarding arrests deemed illegal or misprocedure by the police are one of the urgent issues to be discussed. The legal protection that the parties to this dispute can apply to a defendant who has been the victim of “illegal” arrest by the police in the trial process is pre-trial.